Learning Race: School as a Site of Racialization - Edith Gnanadass (Adult Education Research Conference, 2018)
School is a site of racialization and racism. So, when we engage in anti-racist pedagogy with adults, we need to take into account their racialization in schools and the ensuing implications.
Keywords: Adult Learning; Cultural Historical Activity Theory; Race